Capecitabine and Warfarin Interaction: A Case Report With Review of Literature and Management Options - Althiab, Khalefa; Aljohani, Manal; Alraddadi, Sultan; Algarni, Mohammed (Frontiers in Cardiovascular Medicine, 2022)
Capecitabine is an orally active prodrug of 5-fluorouracil with improved safety and efficacy that is extensively used as an antineoplastic agent. It is converted to 5-Fluorouracil in the liver and tumor tissues. In vitro assays did not reveal any significant potential for interaction between capecitabine and its metabolites with warfarin. However, several reports provided clinical evidence of such interaction resulting in an elevated international normalized ratio (INR) and bleeding. Here, we report another case of capecitabine and warfarin concurrent administration that resulted in sub- or supra- therapeutic INR without any bleeding episode or venous-thromboembolic event through the follow-up period. Moreover, a review of available management options is also presented in this paper.